Faktor-faktor Yang Mempengaruhi Aktivitas Mengikuti Pengajian Dikalangan Remaja Provinsi Lampung : Study Komparatif Terhadap Aktivitas Kelompok Pengajian Rohani Islam Di Perkotaan Dan Pedesaan - Mubasit, Mubasit; Jasmadi, Jasmadi (Jurnal Bimbingan dan Konseling Islam, 2023)
Da'wah Islam is an invitation to follow a religion that is Rahmatan Lil Alamiin, namely a religion that is present in the midst of society and contains an invitation to do good and forbid evil deeds. At present there is a tendency for recitation activities to be "experiencing a decline". Especially among teenagers, this activity also tends to be neglected by the government, society, and families.  Based on research conducted with the subject of this study as many as 91 adolescents who live in villages, namely Way Ratai, Padang Cermin and Punduh Pidada, as well as those who live in urban areas, namely Tanjung Karang Pusat, Teluk Betung Utara, and Kedaton show no effect of increased adolescent activity in the field non-religious to recitation activities with a significance value of 0.201 > 0.005 and t count 1.987 > t table -1.290. For family and community support, it shows an influence on adolescent recitation activities with a significance value of 0.001 <0.05 and an calculated F value of 7.163 > F table 3.099. Further analysis, the significance value for differences in adolescent recitation activities in villages and cities is 0.000 <0.05 and so it can be concluded that there are differences between adolescent recitation activities in villages and cities.